Tradition as a Stepping Stone for a Microbial Defined Water Kefir Fermentation Process: Insights in Cell Growth, Bioflavoring, and Sensory Perception - Köhler, Sarah; Schmacht, Maximilian; Troubounis, Aktino H. L.; Ludszuweit, Marie; Rettberg, Nils; Senz, Martin (Frontiers in Microbiology, 2021)
A process development from a traditional grain-based to a defined water kefir fermentation using a co-culture of one lactic acid bacterium and one yeast was elaborated as a prerequisite for an industrially scalable, controllable and reproducible process. Further, to meet a healthy lifestyle, a low ethanol-containing product was aimed for. Five microbial strains – Hanseniaspora valbyensis, Dekkera bruxellensis, Saccharomyces cerevisiae, Liquorilactobacillus nagelii and Leuconostoc mesenteroides – were used in pairs in order to examine their influence on the fermentation progress and the properties of the resulting water kefir products against grains as a control. Thereby, the combination of H. valbyensis and L. mesenteroides provided the best-rated water kefir beverage in terms of taste and low ethanol concentrations at the same time. As a further contribution to harmonization and reduction of complexity, the usage of dried figs in the medium was replaced by fig syrup, which could have been proven as an adequate substitute. However, nutritional limitations were faced afterwards and thus, an appropriate supplementation strategy for yeast extract was established. Finally, comparative trials in 5 L-scale applying grains as well as a defined microbial consortium showed both water kefir beverages characterized by a pH of 3.14 as well as lactic acid and aromatic sensory properties. The product resulting from co-culturing outperformed the grain-based one, as the ethanol level was considerably lower in favor of an increased amount of lactic acid. The possibility of achieving a water kefir product by using only two species shows high potential for further detailed research of microbial interactions and thus functionality of water kefir.